Analysis Towards the Factor of Inadequacy Retirement Fund Among EPF Members: : A Review Paper - Alias, Azman; Foziah, Nik Hazimi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Aging population has become a global phenomenon. Having a long life is great, but it could turn into a nightmare if not prepared properly, especially for retirement savings. In fact, majority retirees in Malaysia had relied on mandatory retirement scheme organized by Employees Provident Fund (EPF), meanwhile, the funds were estimated to deplete just within 5 years after being given to the retirees. Alternatively, the EPF had provided one of the largest and oldest retirement savings funds in the world. Nevertheless, the retirement funds are still insufficient to cover the monthly payments according to the projected life expectancy of a human being in Malaysia, until 75 years old. Thus, this research aims to examine the analysis towards the factor of inadequacy retirement fund among EPF members. Using content analysis, this research examined the appropriate factors to be considered as the addressed problem. The research found that the retirement planning, financial literacy, money management, unexpected cost of living and social norm during before retirement would be deemed as anchor factors to the highlighted issues. Thus, it is valuable if the future study can focus on those factors in investigating the issues.